Non‐attendance at diabetes outpatient appointments: a systematic review. Issue 9 (3rd February 2020) - Brewster, S.; Bartholomew, J.; Holt, R. I. G.; Price, H.
Abstract: Background: Non‐attendance at diabetes outpatient appointments is a sizeable problem worldwide and has been associated with suboptimal health outcomes. We aimed to describe the characteristics, health outcomes and reasons given for non‐attendance at doctor‐ or nurse‐led diabetes appointments, and interventions to improve attendance. Methods: PubMed, EMBASE, CINAHL and PsychInfo were searched from database inception to February 2019. Included articles were peer‐reviewed, published in English, related to adults or young people with type 1 or type 2 diabetes, and addressed one of the above aspects of non‐attendance. Studies were excluded if reporting on other types of diabetes or reviewing attendance at structured education, retinal screening, paediatric, antenatal, podiatry or dietetic clinics. Results: Thirty‐four studies of varied designs were identified (15 observational, 1 randomized control trial, 9 qualitative, 5 surveys, 4 service improvements). The definition of non‐attendance varied. Younger adults, smokers and those with financial pressures were less likely to attend. Non‐attendance was associated with higher HbA1c ; other outcomes were varied but typically worse in non‐attenders. Reasons for non‐attendance in qualitative studies fell into three categories: balancing the costs and benefits of attendance, coping strategies, and the relationships between the person with diabetes and healthcare professionals. Interventions included appointment management strategies, service improvements, patient navigators and WebCam appointments. Conclusions: Non‐attendance is only partially explained by logistical issues. Qualitative studies suggest complex psychosocial factors are involved. Interventions have progressed from simple appointment reminders in an attempt to address some of the psycho‐social determinants, but more work is needed to improve attendance.